PENGGUNAAN METODA COPRAS (Complex Proportional Assessment) UNTUK MENENTUKAN CALON PEKERJA OPERATOR - Mansyuri, Umar; Hamdan, Hamdan (LPPM Universitas Bina Bangsa, 2023)
The COPRAS method or Complex Proportional Assessment is a method of decision making that assumes direct and proportional dependence of the significance level of alternative uses. Can determine the best solution to the ratio of the worst ideal solution. The need for new workers in the company is very important. For this reason, careful calculations are needed in making decisions. One of the methods used in managing prospective workers is to use the COPRAS (Complex Proportional Assessment) method. The stages of the COPRAS method are: preparing the attributes to be identified, normalizing the matrix, normalizing the weighted matrix, calculating the maximum and minimum index values, calculating the relative weights, and calculating the quantitative utility of each alternative. The conclusion with the COPRAS method in the Decision Support System Prospective workers according to requests, can simplify the process of making reports